The efficacy of Diavite tm (Prosopis glandulosa) as anti-diabetic treatment in rat models of streptozotocin-induced type 1 diabetes and diet-induced-obese insulin resistance - Hill, Cindy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2010.